28. SURVEY OF CLINICAL CHARACTERISTICS AND STRUCTURES IN THE NATURAL CAVITY THAT AFFECT MIDDLE CHANNEL DRAINAGE IN PATIENTS WITH CHRONIC RHINOSINITIS (Vietnam Journal of Community Medicine, 2025)
Objective: to investigate the clinical characteristics and structures in the nasal cavity affecting on midle meatus drainage in patients with chronic rhinosinusitis. Subjects and methods: cross-sectional description of a clinical case series.Results: Among the 183 patients who came for examination, the highest rate of symptom was runny nose 49,7%, nasal congestion 27.3%, head-face heaviness 21.9%, sneezing 1,1%. The rate of nasal mucosa congestion was highest at 73.4%. The majority of cases having septal deformity were 74,3% and concha bullosa was 43,7%. The rate of opaque mucous membrane in the midle meatus was more than 53,6%.Conclusion: Among the patients participating in the study, the highest rate of runny nose and nasal congestion was noted, and the presence of septal deformities was the majority in the patients.
Keywords: septal deviation; facial tension; runny nose; concha bullosa